Islamic Business Ethics in Mobile Credit and Data Package Transactions in The Digital Era: A Fiqh Muamalah Perspective on Mobile Credit Mark-Up Pricing Practices - Jenal Mustofa; Rizal Muttaqin; Rika Rosdiana Effendi (Hikmah, 2026)
This study aims to analyze the pricing (mark-up) practices in mobile phone credit and data package transactions at the CBR 777 Agent in Cibiru Hilir from the perspective of Islamic business ethics and fiqh muamalah. In the digital era, mobile credit and data packages have become essential needs for society; however, the mechanism for determining profit margins at the agent level often raises questions regarding price transparency and fairness. This research employs a qualitative approach using a case study method. Data were collected through field observations, in-depth interviews with the agent owner, employees, and customers, as well as transaction documentation. The findings show that the agent applies a mark-up ranging from IDR 1,500 to IDR 5,000 above the base price to cover operational costs and generate business profit. From the perspective of fiqh muamalah, this practice can be categorized as a bai’ al-musāwamah contract, in which the price is determined through mutual agreement between seller and buyer without the obligation to disclose the original cost. The implementation of Islamic business ethics is reflected in honesty, service responsibility, and transparency in price information. These findings indicate that reasonable and mutually agreed mark-up practices are consistent with the principles of fairness and mutual consent (an-tarāḍin) in Islamic economic transactions.